Kunstmuseum Basel : 150 Gemälde : 12. - 20.Jahrhundert. - Kunstmuseum Basel (Basel : Bâloise-Holding, 1964)
Witz, Konrad ; Schongauer, Martin ; Holbein der Ältere, Hans ; Baldung Grien, Hans ; Manuel Deutsch, Niklaus ; Leu der Jüngere, Hans ; Altdorfer, Albrecht ; Grünewald, Mathias ; Holbein, Ambrosius ; Hug Kluber, Hans ; Stimmer, Tobias ; Schule von Fontainebleau ; van Mieris der Ältere, Frans ; Rigaud, Hyacinthe ; Handmann, Emanuel ; Wolf, Caspar ; Füssli, Johann Heinrich ; de Goya y Lucientes, Francisco ; Corot, Jean-Baptiste-Camille ; Delacroix, Eugène ; Courbet, Gustave ; Böcklin, Arnold ; Buchser, Frank ; Anker, Albert ; Pissarro, Camille ; Monet, Claude ; Sisley, Alfred ; Renoir, Auguste ; Degas, Edgard ; Cézanne, Paul ; Gauguin, Paul ; van Gogh, Vincent ; Hodler, Ferdinand ; Munch, Edvard ; Bonnard, Pierre ; Matisse, Henri ; Derain, André ; Braque, Georges ; Dufy, Raoul ; etc.
boek
Keywords: Basel; Zwitserland